Religion and flourishing among Afro-Trinidadians: the influence of proneness to guilt/shame and forgiveness by God on the relationship between religious commitment and health - Skalski-Bednarz, Sebastian Binyamin; Toussaint, Loren L.; Webb, Jon R.; Wilson, Colwick M.; Worthington, Everett L.; Williams, David R.; Reid, Sandra D.; Surzykiewicz, Janusz (Frontiers in Public Health, 2024)
BackgroundReligiousness has been consistently linked to positive health outcomes and flourishing, yet the underlying mechanisms are complex and not well-understood. The forgiveness and relational spirituality model offers a framework to explore the moderated mediation among religious commitment, health, and forgiveness by God. Understanding these relationships among university students and community residents in Trinidad and Tobago can provide valuable insights into the role of religiousness in promoting wellbeing.Materials and methodsThis cross-sectional study involved 254 religious Afro-Trinidadians aged 18–78 from Trinidad and Tobago. Participants completed measures assessing religious commitment, proneness to guilt/shame, forgiveness by God, and health outcomes. Modeling using 5,000 bootstrap confidence intervals was used to analyze the hypothesized associations among variables.ResultsA significant positive relationship between religious commitment and health encompassed both physical and mental aspects. Feeling forgiven by God mediated the link between religious commitment and health outcomes (B = 0.019; SE = 0.007; 95% CI = 0.007, 0.034; R2 = 0.12). Proneness to guilt or shame moderated the association between religious commitment and forgiveness by God. This relationship was significant primarily among individuals with high levels of proneness to guilt (B = 0.075, SE = 0.019, p < 0.001) and shame (B = 0.074, SE = 0.018, p < 0.001).ConclusionsThis study highlights the importance of religiousness in promoting human flourishing among Afro-Trinidadians residing in Trinidad and Tobago. Religious commitment and forgiveness by God were effective resilience resources that contributed to positive health outcomes. However, the nuanced role of proneness to guilt or shame underscores the need for a deeper understanding of individual differences in emotional responses within religious contexts. Future longitudinal research is warranted to elucidate the dynamic nature of these relationships and inform targeted interventions aimed at enhancing wellbeing in religious communities.